PENGARUH KEPERCAYAAN, KUALITAS LAYANAN DAN PERSEPSI NILAI TERHADAP KEPUASAN PELANGGAN (Studi Pada Pengguna Black Berry Messenger di Fakultas Ekonomi Universitas Syiah Kuala Banda Aceh ) - Saed Armia (JURNAL EKOMBIS, 2018)
Abstract: This  research  motivated by  the  condition  of  competition between  instant message service providers company are increasingly widespread even been able to beat the users of short message service (SMS) in Indonesia.This research purposeful to determine effect of the trust, quality of service and value perception to customer satisfaction on the users of blackberry messenger. Respondents in this research were students  of  economic  faculties  Syiah  Kuala  University  Banda  Aceh  users  of blackberry messenger as 100 people. The sampling technique used in this research is the purpose sampling. Analysis in this research used multiple linear regression.The results of this research stated that partially trust, quality of service and value perception have positive effect and significant to customer satisfaction. Based on the result showed that the variable of value perception have the biggest effect that is 36 percent with significance 0,000 Adjusted R square 0.364 showed that 36.4 percent of the variance of customer satisfaction is explained by independent variable in the regression equation, while the other 64.6 percent is explained by other variables not examined in this research.Keywords: Trust, Service Quality, Perceived Value, Customer Satisfaction.